THE PHYSICAL AND NON-PHYSICAL ASPECTS OF THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Zacharias Tehubijuluw (JURNAL BADATI, 2024)
This research aims to determine, test and analyze the influence of the physical and non-physical work environment on employee performance at the Central Maluku Regency Investment and One- Stop Integrated Services Service. This research uses a descriptive-quantitative approach with a correlational cause-effect type. The population used in this research were all 28 employees of the Central Maluku Regency Investment and One-Stop Integrated Services Service, consisting of 26 civil servants and 2 honorary staff. The sampling method is full sampling. Data were analyzed using multiple linear regression analysis with the help of SPSS22.00 software. The results of the research concluded that (1) The physical work environment had a positive and significant effect on the performance of employees of the Central Maluku Regency Investment and One- Stop Integrated Services Service; (2) The non-physical work environment has a positive and significant effect on the performance of employees of the Central Maluku Regency Investment and One-Stop Integrated Services Service; (3) The physical and non-physical work environment has a positive and significant effect on the performance of employees of the Central Maluku Regency Investment and One-Stop Integrated Services Service